Electrode tips geometry and penetrating in narrow gap welding. (1st April 2013) - Sun, Q J; Hun, H F; Li, W J; Liang, Y C; Feng, J C
<x xml:space="preserve">Abstract</x> The problem of sidewall incomplete fusion in narrow gap tungsten inert gas (TIG) welding could be well solved when the proper magnetic field was added. However, the various tungsten electrode tips seriously affect the distribution of arc pressure and the quality of welding seams. In addition, it is a 350 A GTA, as this is in a regime in which finger penetration is common. This paper studies the distribution of arc pressure of five different styles of tungsten electrode tips: 30° circular cone, 60° circular cone, 60° circular cone with truncated cone of 2 mm diameter, terrace of 2×2 mm and terrace of 2×0·8 mm with the same welding parameters. The character of arc pressure is verified by assaying the seam cross-section under the controlling magnetic field condition in narrow gap welding. The measuring equipment that we designed independently is creative and applicative in narrow gap TIG welding under magnetic fields.